Evaluation of Crosslinking on the Water Sorption Properties of Poly(Vinyl) Alcohol (2015)
ABSTRACT: Poly (vinyl) alcohol has the ability to sorb water depending on the degree of hydrolysis and its molecular weight. Thus, a low molecular weight PVA is expected to have more water solubility and more water sorbing properties. These properties could also be affected by the crosslinking conditions employed. In this study, PVA crosslinked with glutaraldehyde at the 1:10 and 1:5 PVA to GA ratios for 1 and 6h at 70 °C and a pH of 5.5 and 6.5 was conducted followed by precipitation and washing with acetone and further drying. The resulting films were exposed to water activities from 0 to 0.9 and submitted to swelling and contact angle studies. All materials exhibited a type III isotherm shape. Crosslinking induced the formation of a more porous material with a low sorption capacity as compared to the parent material. Further, the low water uptake diffused in those films explained their low water swelling capacity.